Pengaruh Model Pembelajaran Realistic Mathematic Education Terhadap Kemampuan Berpikir Kritis Matematis Siswa SMP - Samron, Samron; Safarudin (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2022)
Entering the life of the industrial revolution 4.0, high-level abilities must be possessed by every student including the ability to think critically in mathematics. Developing and improving students' mathematical critical thinking skills requires a learning model that can provide flexibility for students to develop ideas by relating students' real lives. The learning model that relates the real life of students in the learning process is the realistic mathematics education learning model. The purpose of this study was to determine the effect of the realistic mathematics education learning model on the mathematical critical thinking skills of junior high school students. This type of research is a quasi-experimental research with a pretest-posttest control group design in class VIII SMP Negeri 9 Baubau as many as 2 classes consisting of 1 experimental class and 1 control class. Sampling using purposive sampling technique. Data were analyzed using t-test analysis. The results showed: (1) the realistic mathematics education learning model had an effect on increasing students' mathematical critical thinking skills; (2) the realistic mathematics education learning model has a better effect than conventional learning models on increasing the mathematical critical thinking skills of junior high school students.